Production of extruded snacks by utilization of watermelon (Citrullus vulgaris) seed flour - Raja, M Praveen; Karthiayani, A; Selvan, P; Nithyalakshmi, V (Journal of Postharvest Technology, 2019)
Watermelon (Citrullus vulgaris) seed is one of the under-utilized oil seed which has good nutritional value like protein, minerals and unsaturated fatty  acids. The extruded snacks were prepared by incorporation of watermelon seed flour in rice-corn flour blend. The dehulled watermelon seed was  milled into flour and incorporated into rice-corn blend at 10, 15 and 20% proportions for the preparation of extruded snacks. The optimal level of  incorporation of watermelon seed flour (WSF) in extruded snacks was found to be 15% (w/w) based on evaluation of physical and sensory  characteristics of the extrudates. The extruded snacks prepared using this optimal formulation was packed by nitrogen flushing and studied for  properties such as proximate composition peroxide value, hardness, colour (L*, a*and b*) and sensory characteristics during 90 days of storage and  compared with control extruded snacks based on rice-corn flour blend. As a result, the WSF incorporated extruded snacks was found to remain in  good condition till the end of storage period.
Keywords: extruded snacks; fortification; storage study; utilization; watermelon seed flour